The Role of Local Government in Road Maintenance From the Perspective of Siyasah Tanfidziyah (A Study in Palembayan Subdistrict, Agam Regency) - Rahmani, Gina; Wirman, Hardi Putra (International Journal of Education, Information Technology, and Others, 2025)
This inquiry endeavors to elucidate the function of regional governance in the sustenance of roadway infrastructure within Palembayan Subdistrict, Agam Regency, while concurrently evaluating its enactment through the theoretical prism of siyāsah tanfīdhiyyah in Islamic political jurisprudence. The principal concern addressed pertains to the extent of the local government's fidelity in executing its mandate to preserve public infrastructure as a constituent of essential civic services, and whether such endeavors resonate with the normative values of equity, fiduciary integrity, and collective welfare as expounded in the doctrine of al-sulṭah al-tanfīdhiyyah. Adopting a qualitative paradigm, this study garnered data via empirical observation, exhaustive interviews with stakeholders from the Department of Public Works, subdistrict administration, nagari authorities, and the resident populace, as well as document analysis. The empirical evidence reveals that, although local authorities have instituted various periodic and routine programs for road maintenance, the execution remains disparate and less than efficacious. This predicament arises from fiscal insufficiency, a paucity of skilled personnel, and anemic coordination across bureaucratic entities. Within the framework of siyāsah tanfīdhiyyah, the regional government is called not merely to administer policies but to act as a conscientious steward of the public mandate, imbued with the ethical imperatives of Islamic law namely distributive justice, procedural openness, and unwavering accountability for communal prosperity. Thus, a recalibration of strategic intent and a more resolute institutional commitment are deemed requisite for achieving comprehensive and Sharia-compliant infrastructure stewardship.